INTERAKSI SOSIAL KELOMPOK MASYARAKAT ISLAM & KRISTEN DI KELURAHAN BOMBONGAN, KECAMATAN MAKALE, KABUPATEN TANA TORAJA - Syamsul Alam; Dian Nur Anna (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2021)
What the community wants is to live side by side, accept each other, respect each other, help each other and work together between religious adherents. Life that takes place dynamically sometimes causes friction which then leads to conflict or conflict. In Bombongan Village, Makale District, Tana Toraja Regency. harmonious relationship has been created between Muslim and Christian communities, this is based on forms of social interaction such as the use of the same local language in communication, mutual need in terms of work and the economy, and social gatherings.